¬PENERAPAN MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN MINAT BELAJAR IPA FISIKA SISWA DI KELAS VIIIB MTs DINIYAH PUTRI PEKANBARU - Oktaria, Neri Oktaria; ', Zulhelmi; Nor, Muhammad Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study aimed to describe and know that through the implementation of cooperative models Numbered Head Together (NHT) can increase students' interest in science learning in the classroom physics VIIIB MTs Diniyah Putri Pekanbaru on the material pressure. Research subjects in this study were all students in grade VIIIB MTs Diniyah Putri Pekanbaru 2014/2015 school year as many as 23 students. The research design is One Group Pretest-Posttest Design. The technique of collecting data is questionnaires and documentation techniques, data collected in this study are primary data and secondary data. Data were analyzed by using descriptive analysis and inferential analysis. Descriptive analysis was obtained: 1) The interest of student learning in class VIIIB MTs Diniyah Putri Pekanbaru with the implementation of the cooperative model NHT in physics science learning is increased. 2) There is a change of physics students 'interest in science learning in the material pressure for 11.60% by using the implementation of the cooperative model NHT VIIIB class Diniyah Putri Pekanbaru, and inferential analysis results obtained are significant increase students' interest in science learning physics through the implementation of the cooperative model NHT VIIIB class MTs Diniyah Putri Pekanbaru. Key Words:Interests Of Learning Physics IPA, Numbered Head Together, Inferential Analysis